Toward High Solar Cell Efficiency with Low Material Usage: 15% Efficiency with 14 μm Polycrystalline Silicon on Glass. Issue 6 (20th March 2020) - Garud, Siddhartha; Trinh, Cham Thi; Abou-Ras, Daniel; Stannowski, Bernd; Schlatmann, Rutger; Rech, Bernd; Amkreutz, Daniel
Abstract : Liquid‐phase‐crystallized silicon (LPC‐Si) is a bottom‐up approach to creating solar cells with the potential to avoid material loss and energy usage in wafer slicing techniques. A desired thickness of silicon (5–40 μm) is crystallized with a line‐shaped energy source, which is a laser, herein. The first part reports the efforts to optimize amorphous silicon contact layers for better surface passivation. The second part covers laser firing on the electron contact. It enables a controllable trade‐off between charge collection and fill factor (FF) by creating a low resistance contact, while preserving a‐Si:H (i) passivation in other areas. Short‐circuit current density ( J SC ) is observed to be up to 33:1 mA cm −2, surpassing all previously reported values for this technology. Open‐circuit voltage ( V OC ) of up to 658 mV also exceeded every previous value published at a low bulk doping concentration (1 × 10 16 cm −3 ). Laser firing reduced J SC by 0:6 mA cm −2 on average but improved the FF by 22.5% absolute on average, without any significant effect on V OC . Collectively, these efforts have helped in achieving a new in‐house record efficiency for LPC‐Si of 15.1% and show a potential to reach 16% efficiency in the near future with optimization of series resistance. Abstract : A bottom‐up approach to creating silicon solar cells using a line‐shaped laser is displayed. Efforts to create thicker amorphous silicon passivation and contact layers as well as laser firing for low contact resistance are reported. Collectively, a new in‐house record efficiency of 15.1% is achieved along with a clear pathway to reach 16% efficiency with optimization of series resistance.